Women’s Experience with Obstetric Violence during Hospital Birth - Sughra Abbasi, Sadia Suboohi Sadiq, Samina Naz, Sumiyya Khalid, Amina Bukhari (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The purpose of this study was to investigate obstetric violence in a Public Hospital. Materials and Methods: This Cross-sectional study was performed at department of Obstetrics and Gynecology Government hospital in Karachi for one-year, from January 2020 to January 2021. Non-probability consecutive sampling technique was used for participants’ selection and 200 patients were included. Data were collected on maternal and demographic characteristics, recent birth experiences and obstetric violence. Results: The data of 200 participants were analyzed. The mean age (SD) of females in this analysis was 32.10 (7.20) years. About 75 percent of those surveyed said staff did not allow family members to attend the patient during birth. The most reported physical abuse was staff members who did vaginal examination painfully during delivery (40.5%), staff who pressed the abdomen during delivery (29.5%) and was not gentle, and staff who underwent episiotomy without anesthesia (25.5%). When asked about negligent care/ Abandonment, 108 (54%) reported experiencing screaming or blaming from the authorities during childbirth, while 97(48.5%) reported negative feedback or received threats from the authorities during childbirth. 97 people (48.5%) reported Non confidential care. In addition, about 71(35.5%) of women reported Non dignified care during childbirth, and 68 (34%) reported Non consented care. Physical abuse was reported in 36(18.0%) patients and bribe taken from 10 patients (5%). Conclusion: Women during pregnancy were subjected to non-dignified care as an invasive method, drug use was not mandatory, their privacy was violated, they were largely exposed to physical violence and the needs of pregnant women were ignored.